The two-dimensional finite element/boundary element method in electromagnetics : formulation, applications, error estimates and mesh adaptive procedures - Meyer, Frans J. C.(Frans Johannes Christiaan) (Stellenbosch : Stellenbosch University, 2012)
Dissertation (Ph. D.) -- University of Stellenbosch, 1994.